State regulation of the securities market of the Republic of Kazakhstan - Yelshibayev, R.K.; Sauranbai, S.B.; Agymbai, A.O. (BUKETOV BUSINESS REVIEW, 2021)
Object: The purpose is to identify promising directions for the development of the securities market of the Republic of Kazakhstan and reform the system of its government regulation. Methods: The study used methods of empirical, subject-object, system, deductive and comparative analysis. Each of these methods was used adequately to its functional capabilities and resolving abilities for solving the corresponding stage research tasks. Findings: As a result of the research by the author: - features of the securities market as an object of government regulation are studied; - infrastructure support of the system of government regulation of the securities market of the Republic of Kazakhstan was examined; - assessment of the current state of the securities market of the Republic; - system problems of government regulation and market development are investigated; - promising areas of reforming the securities market of the Republic of Kazakhstan and its government regulation system are developed and scientifically substantiated. Conclusions: A shift of focus from problems of legal support of the system of government regulation of the securities market of the Republic of Kazakhstan to the problem of primary transparency and reliability of the market in terms of economic integration and global coronacrisis will allow achieving the following targets: - share market capitalization to GDP will double if new IPOs are held by corporate issuers; - RFCA will join the group of ten leading financial centers in Asia; - access to financial services for a wide range of consumers will be provided; - increase of financial literacy of the population, protection of interests of potential investors and safety of savings of market participants will be ensured